A Case Report on Diabetes Mellitus with Holistic Approach (AYUSHDHARA, 2025)
This case report presents the successful management of an elderly patient with uncontrolled diabetes, hypertension, and associated urinary complaints using Ayurvedic interventions. The treatment approach included Kathakakhadiradi Kashaya, Ashwagandha Churna, and Madhuhara Churna, targeting both metabolic regulation and stress reduction. The patient initially presented high HbA1c levels (11.7%) and mean blood glucose of 289.09mg/dL. A treatment regimen focusing on Deepana, Pachana, Lekhana, and Medohara therapies was implemented. After nine months of Ayurvedic intervention, HbA1c dropped to 4.9%, with significant improvements in glycemic control and overall well-being. The patient also reported complete relief from urinary symptoms. The herbal formulations demonstrated notable efficacy in restoring pancreatic function, enhancing insulin secretion, reducing insulin resistance, and mitigating stress-induced hyperglycemia. The adaptogenic properties of Ashwagandha further contributed to stress reduction, improving glycemic stability. No adverse effects were observed, and the patient continues to be monitored for potential reduction in conventional oral anti-hyperglycemic medications. This case highlights the potential of Ayurvedic formulations as an effective complementary approach in diabetes management. The integration of Kathakakhadiradi Kashaya, Ashwagandha, and Madhuhara Churna presents a promising natural alternative for improving glycemic control, reducing complications, and enhancing overall metabolic health in diabetic patients.